Metallothionein and Superoxide Dismutase-Antioxidative Protein Status in Fullerene-Doxorubicin Delivery to MCF-7 Human Breast Cancer Cells - Kepinska, Marta; Kizek, Rene; Milnerowicz, Halina (International journal of molecular sciences, 2018)
Doxorubicin (DOX) is one of the most frequently used anticancer drugs in breast cancer treatment. However, clinical applications of DOX are restricted, largely due to the fact that its action disturbs the pro/antioxidant balance in both cancerous and non-cancerous cells. The aim of this study was to investigate the influence of fullerene (C60) in cell treatment by DOX on the proliferation of human breast cancer cells (MCF-7), concentration of metallothionein (MT) and superoxide dismutase (SOD), and SOD activity in these cells. The use of C60 in complexes with DOX causes a change in the level of cell proliferation of about 5% more than when caused by DOX alone (from 60⁻65% to 70%). The use of C60 as a DOX nanotransporter reduced the MT level increase induced by DOX. C60 alone caused an increase of SOD1 concentration. On the other hand, it led to a decrease of SOD activity. C60 in complex with DOX caused a decrease of the DOX-induced SOD activity level. Exposure of MCF-7 cells to DOX-C60 complexes results in a decrease in viable cells and may become a new therapeutic approach to breast cancer. The effects of C60 in complexes with DOX on MCF-7 cells included a decreased enzymatic (SOD activity) and nonenzymatic (MT) antioxidant status, thus indicating their prooxidant role in MCF-7 cells.
Keywords: doxorubicin; Metallothionein; nanoparticles, metallothionein; protinádorové látky; Cell Proliferation; fullereny; superoxiddismutasa 1; Nanoparticles; metalothionein; nanočástice; superoxide dismutase; MFC-7 buňky; breast tumors; MCF-7 Cells; Superoxide Dismutase-1; fullerene; lidé; Humans; drug delivery systems; proliferace buněk; Doxorubicin; Antineoplastic Agents; Fullerenes